2017
DOI: 10.3168/jds.2017-12574
|View full text |Cite
|
Sign up to set email alerts
|

Technical note: Nontargeted detection of adulterated plant proteins in raw milk by UPLC-quadrupole time-of-flight mass spectrometric proteomics combined with chemometrics

Abstract: We built and validated a chemometric model to detect possible milk adulteration with plant proteins. Specifically, we extracted proteins in raw milk, treated with tryptic digestion, and obtained peptide fingerprints by UPLC-quadrupole time-of-flight-mass spectrometry with proteomics to differentiate authentic milks from their counterparts adulterated with nonmilk proteins. This approach is able to detect soybean and pea powder-adulterated milks at as low as 1% (wt/wt). Additionally, we obtained the characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…An approximate linear relationship of data points dependent on protein levels could be observed for samples adulterated with SP. Results of PCA in the current study are similar to those reported in other literature (Cordewener et al., ; Lu et al., ). Our results show that the adulterated samples could be separated from authentic milk for adulterants proteins.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…An approximate linear relationship of data points dependent on protein levels could be observed for samples adulterated with SP. Results of PCA in the current study are similar to those reported in other literature (Cordewener et al., ; Lu et al., ). Our results show that the adulterated samples could be separated from authentic milk for adulterants proteins.…”
Section: Resultssupporting
confidence: 92%
“…In the loading plot (Figure 3b are similar to those reported in other literature (Cordewener et al, 2009;Lu et al, 2017). Our results show that the adulterated samples could be separated from authentic milk for adulterants proteins.…”
Section: Lc-ms/ms Coupled With Multivariable Statisticssupporting
confidence: 88%
See 3 more Smart Citations